Test the Effectiveness of Rose Flower Water ( Rosa Damascena Mill) As a Potential Herbal Drink Health - Purwanto, Diyan Sakti; Setiyanto, Riyan; Arsela, Putri (Universitas Pahlawan Tuanku Tambusai, 2024)
Roses (Rosa damascena Mill) are a commodity that has economic value that is not utilized optimally. Research on roses shows that roses have potential as a source of natural antioxidants. Some of the chemicals contained in roses include tannin, geraniol, nerol, citronellol, geranic acid, terpenes, flavonoids, pectin polyphenols, vanillin, carotenoids, stearopten, farnesol, eugenol, phenylethyl alcohol, vitamins B, C, E, and K. There is a need for further research regarding the active compounds contained in rose water which can have the potential to be used as a herbal drink for human health that meets standards by showing appropriate tests. The aim of this research is to determine the value, total flavonoids and vitamin C value in waste and rose water. This research was designed with stages of determination of rose plants, preliminary tests, phytochemical screening of rose waste and water including: organoleptic observations, total flavonoids and vitamin C. From the research, it was found that the total value of flavonoids in mamar flower waste water was 1.24 ± 0.03, while in rose water it was 0.68 ± 0.02. The main flavonoid compound is quercetin which consists of lutein, luteoxanthin and ?-carotene and is correlated with antioxidant activity. The level of Vitamin C in C rose flower waste is 0.314 ± 0.0028, while in rose water it is 0.244 ± 0.0009, this is due to the ascorbic acid content. From the results, the value of vitamin C shows a correlation with flavonoids. The higher the flavonoid value, the higher the vitamin C value. With the flavonoid and vitamin C content, rose flower waste and water have the potential as a health herbal drink.